MENGEMBANGKAN ENTREPRENEURSHIP SEJAK USIA DINI MELALUI KEGIATAN MARKET DAY - Iis Susanti; Washilla, Fadhilla; Yetri; Badarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the era of global disruption and uncertain economic dynamics, fostering an entrepreneurial spirit from an early age is no longer just an option, but a strategic urgency. Early childhood education plays a crucial role as the foundation for character and mindset formation.